Do only children have poor vision? Evidence from China's One‐Child Policy. (23rd April 2018) - Zhao, Liqiu; Zhou, Minghai
Abstract: This paper examines whether only children have poor vision by exploiting the quasinatural experiment generated by the Chinese One‐Child Policy. The results suggest that being an only child increases the incidence of myopia by 9.1 percentage points. We further investigate the mechanisms through which being an only child affects the myopia and find that only children, as the only hope in a household, receive higher expectations in terms of academic performance and future educational attainment and pressure to succeed in life from parents, which contribute to the increased myopia. We also find that the school quality of only children is significantly higher than that of non‐only children. This study provides new insights into an important health consequence of One‐Child Policy in China.